Enhanced properties of poly(silylene phenylether arylacetylene) by a side cyano group. Issue 9 (6th July 2022) - Li, Chuan; Ma, Manping; Tang, Junkun; Yuan, Qiaolong; Huang, Farong
Abstract: Poly(silylene arylacetylene) resin is a type of thermosetting resin with high heat resistance and good mechanical performance. A cyano group was introduced into a 1, 3‐bis(4‐ethynylphenoxy)benzene, and thus a poly(silylene phenylether arylacetylene) with a side cyano group (PCNSA‐MP) was obtained by the polymerization of 2, 6‐bis‐(4‐ethynylphenoxy)benzonitrile and dichlormethylphenylsilane under a catalyst. The structures and properties of PCNSA‐MP and poly(silylene phenylether arylacetylene) (PSEA‐MP) resins and the mechanical properties of T300/resin composites were studied. The results show that both PCNSA‐MP and PSEA‐MP resins possess good heat resistance. Especially, the PCNSA‐MP resin with the cyano group exhibits lower curing temperature, better heat resistance, and higher mechanical properties as compared with PSEA‐MP resin. The T d5 of the cured PCNSA‐MP resin arrives at 491°C and there is no significant glass transition below 450°C for the resin. The flexural strengths of the cured PCNSA‐MP resin and T300/ PCNSA‐MP composite reach 55.2 MPa and 433.8 MPa, respectively. Abstract : The side cyano group enhances the mechanical properties of the cured poly(silylene phenylether arylacetylene) and its composite